Investigating the Relationship between Characteristics of a Good Teacher and Academic Engagement with Mediation of Academic Buoyancy of Graduate Students - Atefeh Ghenaati; Naser Nastiezaie (Zanjan University of Medical Sciences and Health Services, 2019)
Background and Objective: One of the major education quality indicators is students' academic engagement, which could be influenced by students' academic buoyancy and effective teacher features. The present study aimed to investigate the relationship between effective teacher features and academic engagement mediated by academic buoyancy of post-graduate students at Sistan and Baluchestan University. Materials and Methods: This research is applied in terms of objective and a structural equation-based correlational study in terms of research method. Using stratified random sampling method and according to Cochran's sampling formula, 341 postgraduate students were included in the study and filled in three questionnaires of effective teacher features, academic engagement, and academic buoyancy. Correlation coefficient of the structural equation model was used to analyze the data. SPSS software version 16 and LISREL software were used to run the analyses. Results: There were significant correlation coefficients between the effective teacher features and academic engagement (r = 0.56, p <0.001), effective teacher features and academic buoyancy (r = .328 p <0.001), academic buoyancy and academic engagement (r=0.486, p <001). The direct effects of the effective teacher features on academic engagement (t =8.02, β = 0.98), effective teacher features on academic buoyancy (t =4.23, β =0.45) and academic buoyancy on academic engagement (t =4.43, β = 0.45) were significant. The indirect effect of the effective teacher features on academic engagement with regard to the mediating role of academic buoyancy (β = 0.157) was also significant. Conclusion: University professors can enhance the academic buoyancy and academic engagement of their students through employing cultural-educational, training, research and service-executive indicators.